The Australasian Resuscitation In Sepsis Evaluation: Fluids or vasopressors in emergency department sepsis (ARISE FLUIDS), a multi‐centre observational study describing current practice in Australia and New Zealand. (10th February 2020) - Keijzers, Gerben; Macdonald, Stephen PJ; Udy, Andrew A; Arendts, Glenn; Bailey, Michael; Bellomo, Rinaldo; Blecher, Gabriel E; Burcham, Jonathon; Coggins, Andrew R; Delaney, Anthony; Fatovich, Daniel M; Fraser, John F; et al.
Abstract: Objectives: To describe haemodynamic resuscitation practices in ED patients with suspected sepsis and hypotension. Methods: This was a prospective, multicentre, observational study conducted in 70 hospitals in Australia and New Zealand between September 2018 and January 2019. Consecutive adults presenting to the ED during a 30‐day period at each site, with suspected sepsis and hypotension (systolic blood pressure <100 mmHg) despite at least 1000 mL fluid resuscitation, were eligible. Data included baseline demographics, clinical and laboratory variables and intravenous fluid volume administered, vasopressor administration at baseline and 6‐ and 24‐h post‐enrolment, time to antimicrobial administration, intensive care admission, organ support and in‐hospital mortality. Results: A total of 4477 patients were screened and 591 were included with a mean (standard deviation) age of 62 (19) years, Acute Physiology and Chronic Health Evaluation II score 15.2 (6.6) and a median (interquartile range) systolic blood pressure of 94 mmHg (87–100). Median time to first intravenous antimicrobials was 77 min (42–148). A vasopressor infusion was commenced within 24 h in 177 (30.2%) patients, with noradrenaline the most frequently used ( n = 138, 78%). A median of 2000 mL (1500–3000) of intravenous fluids was administered prior to commencing vasopressors. The total volume of fluid administered from pre‐enrolment to 24 h was 4200 mL (3000–5661), with a range from 1000 to 12 200 mL. Two hundred and eighteen patients (37.1%) were admitted to an intensive care unit. Overall in‐hospital mortality was 6.2% (95% confidence interval 4.4–8.5%). Conclusion: Current resuscitation practice in patients with sepsis and hypotension varies widely and occupies the spectrum between a restricted volume/earlier vasopressor and liberal fluid/later vasopressor strategy.